The potential of B-Star snacks (banana and tempeh nastar) to prevent muscle fatigue - Ni Made Dewantari; G.A. Dewi Kusumayanti; Hertog Nursanyoto; Ketut Lilik Arwati (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Muscle fatigue is a common problem experienced by athletes when undergoing exercise. Sports snacks are an effective solution for preventing them because they can be consumed between workouts without requiring a particular time. However, the availability of sports snacks is still rarely traded in the market. The purpose study is to produce a nastar based on a mixture of banana flour and tempeh (named B-Star Snack) as a sports snack that can prevent muscle fatigue. The research was carried out in July - December 2020 at the Food Technology Lab, Department of Nutrition, Denpasar Health Polytechnic, where wheat flour as the main ingredient for making nastar was substituted with tempeh flour and banana flour with the five combinations of banana flour and tempeh mixtures. All observations were analyzed by ANOVA. Especially for the results of the organoleptic test, in order to meet the assumption of a normal distribution, the data is transformed into an interval scale using the successive interval method. There was a significant difference in the preference for B-Star Snack between formulas (p = 0,014). The most preferred is the combination of tempeh and banana flour (40:60%). The B-Star Snack with a 40:60% combination contains the complete nutrition of both macro and micronutrients. The B-Star Snack with a tempeh and banana flour 40:60% as much as 100 grams per serving can be recommended to prevent muscle fatigue due to the exercise.